Ear Nose and Throat Manifestations of Tuberculosis: A Cross-Sectional Study at Tertiary Care Hospital - Abdul Manan Khan, Aria Masoom (Pakistan Journal of Medical & Health Sciences, 2023)
Background: TB is a chronic, granulomatous, infectious, and communicable illness that is caused by the Mycobacterium tuberculosis. Tuberculosis can affect many other organs in the body, but it mostly affects the lungs. Objective: The aim of the study was to determine the Ear Nose and Throat manifestation in patients of tuberculosis Methodology: This study was carried out at the Department of ENT, Bolan Medical College / Complex Hospital, Quetta from December 2022 to May 2023 after taking approval from the research committee of the institute. A randomized sampling approach was used in the study to choose the participants. Out of 160 patients, only 100 individuals who had been diagnosed with head and neck lesions or extrapulmonary tuberculosis (TB) in the ENT region were included in the research. There was a comprehensive, systemic, and general ENT evaluation. An X-ray of each person’s chest was taken in posteroanterior (PA) view. Endoscopic techniques such otoendoscopy, diagnostic nasal endoscopy, and direct laryngoscopy were performed as needed. An ultrasonography neck examination and fine needle aspiration cytology (FNAC) were performed on all individuals who had suspected neck swelling. SPSS version 23 was used for data analysis. Results: A total of 160 patients were enrolled in the current study. Only 100 (62.5%) of the 160 TB patients were found to have ENT symptoms. 60 (60%) of them were male, and 40 (40%) were female. In the area of the ENT, TB of lymphadenopathy has been shown to be the most common lesion 80 (80%) in extra-pulmonary TB patients. The most common symptoms were neck swelling 32 (32%), and fever 48 (48%). Even though pulmonary TB was the most common co-morbidity, 18 (18%) whereas 60 (60%) did not have any co-existing conditions. Conclusion: Our study concluded that the extra pulmonary TB is a prevalent (63%) condition. TB lymphadenitis continues to be the most common manifestation in the head and neck region. Keywords: Ear; Nose; Throat; Manifestations; Tuberculosis